2012
DOI: 10.5194/acp-12-10925-2012
|View full text |Cite
|
Sign up to set email alerts
|

A multi-instrument comparison of integrated water vapour measurements at a high latitude site

Abstract: Abstract. We compare measurements of integrated water vapour (IWV) over a subarctic site (Kiruna, Northern Sweden) from five different sensors and retrieval methods: Radiosondes, Global Positioning System (GPS), ground-based Fourier-transform infrared (FTIR) spectrometer, groundbased microwave radiometer, and satellite-based microwave radiometer (AMSU-B). Additionally, we compare also to ERA-Interim model reanalysis data. GPS-based IWV data have the highest temporal coverage and resolution and are chosen as re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 36 publications
7
67
0
Order By: Relevance
“…Each of these techniques has their strengths and weaknesses, and need to be inter-compared carefully under different conditions if progress is to be made on understanding the water vapour distribution and its time variability. Buehler et al (2012) concluded that a literature survey reveals that reported systematic differences between different techniques are study-dependent and show no overall consistent pattern. Further improving the absolute accuracy of IWV measurements and providing climate-quality time series therefore remain challenging problems.…”
Section: R Van Malderen Et Al: a Multi-site Iwv Intercomparisonmentioning
confidence: 97%
See 4 more Smart Citations
“…Each of these techniques has their strengths and weaknesses, and need to be inter-compared carefully under different conditions if progress is to be made on understanding the water vapour distribution and its time variability. Buehler et al (2012) concluded that a literature survey reveals that reported systematic differences between different techniques are study-dependent and show no overall consistent pattern. Further improving the absolute accuracy of IWV measurements and providing climate-quality time series therefore remain challenging problems.…”
Section: R Van Malderen Et Al: a Multi-site Iwv Intercomparisonmentioning
confidence: 97%
“…Although an IWV multiinstrument intercomparison has been the subject of at least a dozen of papers in the literature (see Buehler et al, 2012, for a number of these, and Hocke and Martine, 2013, for tables of intercomparison studies), the added value of our analysis lies in focusing on homogeneous data sets or data sets taking part in a homogenisation procedure. Moreover, several studies in the literature concentrate on a multi-sensor intercomparison at a single site (e.g.…”
Section: R Van Malderen Et Al: a Multi-site Iwv Intercomparisonmentioning
confidence: 99%
See 3 more Smart Citations